Black African Postgraduate Students' Authorial Voice in Scholarship - Pietersen, Doniwen; Dube, Mbusiseni Celimpilo (Research in Social Sciences and Technology, 2024)
In this theoretical paper we explore the authorial voice of black African postgraduate students in their writing and scholarship experience. This includes investigating the undergirding factors that need to be interrogated when it comes to the student–supervisor relationship. Some (if not most) black African postgraduate students experience challenges in respect of expressing or formulating that all-important authorial voice in their studies, possibly due to a failure to convey ideas, thoughts and arguments systematically. In addition, cultural identity and academic requirements may be hindrances, making it more difficult for them to write successfully, and to engage appropriately in their postgraduate research journeys. In the process of postgraduate students unearthing their authorial voice, a qualitative approach was adopted in this desktop study. In terms of the theoretical framework, the critical pedagogy of Freire was used to examine this phenomenon. Freire’s theory underscores the fact that supervisors cannot simply see themselves imposing their views on those who are less knowledgeable about authorial voice. The findings of this work lean towards highlighting that the student, to a large degree, are to be blamed for this oversight, because without giving students any agency in the supervision journey, supervisors tend to reproduce their experience.